2009
DOI: 10.1002/mnfr.200800473
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydrolysates from β‐conglycinin enriched soybean genotypes inhibit lipid accumulation and inflammation in vitro

Abstract: Obesity is a worldwide health concern and a well recognized predictor of premature mortality associated with a state of chronic inflammation. The objective was to evaluate the effect of soy protein hydrolysates (SPH) produced from different soybean genotypes by alcalase (SAH) or simulated gastrointestinal digestion (SGIH) on lipid accumulation in 3T3-L1 adipocytes. The anti-inflammatory effect of SPH produced by alcalase on LPS-induced macrophage RAW 264.7 cell line was also investigated. SAH (100 microM) deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Some isoflavones are potent dual PPARα/γ agonists and/or aryl hydrocarbon receptor (AhR) agonists and induce cell cycle arrest and modulate xenobiotic metabolism (Medjakovic et al 2010). Moreover, soy protein hydrolysates can decrease expression of inflammatory genes in vitro (Martinez-Villaluenga et al 2009) and, more importantly have potential clinical applications, in vivo (Nagarajan et al 2008). Further therapeutic potential is present in soy-derived di-and tripeptides which have shown recent promise in alleviating colon and ileum inflammation, in vivo (Young et al 2012).…”
Section: Traditional Medical Uses For Sweet Potato For a Modern Agementioning
confidence: 99%
“…Some isoflavones are potent dual PPARα/γ agonists and/or aryl hydrocarbon receptor (AhR) agonists and induce cell cycle arrest and modulate xenobiotic metabolism (Medjakovic et al 2010). Moreover, soy protein hydrolysates can decrease expression of inflammatory genes in vitro (Martinez-Villaluenga et al 2009) and, more importantly have potential clinical applications, in vivo (Nagarajan et al 2008). Further therapeutic potential is present in soy-derived di-and tripeptides which have shown recent promise in alleviating colon and ileum inflammation, in vivo (Young et al 2012).…”
Section: Traditional Medical Uses For Sweet Potato For a Modern Agementioning
confidence: 99%
“…Soy phytochemicals such as isoflavones (11,12) and saponins (13) and proteins, including Bowman-Birk trypsin inhibitors (14) and lunasin (15), have been reported to reduce inflammation. Recently, soy protein hydrolysates were shown to reduce the expression of inflammatory genes in vitro (16) and in vivo (17). Although antiinflammatory soy di-or tripeptides have not yet been reported, to our knowledge, past studies of bioactive soy peptides (18,19) suggest that with the aid of peptide transporter 1 and paracellular intestinal transport (20), these peptides can cross the intestinal barrier, arrive in an intact form, and exert bioactivity at the target site.…”
Section: Introductionmentioning
confidence: 96%
“…A dietary study performed using a β-conglycinin enriched genotype of soybean has suggested the importance of this protein for hypocholesterolaemic activity (Martinez-Villaluenga, Dia, Berhow, Bringe, & de Mejia, 2009). Some investigations have shown that its α′ subunit may have a major role in the cholesterol-lowering properties of soybean (Consonni et al, 2010(Consonni et al, , 2011Duranti et al, 2004).…”
Section: Introductionmentioning
confidence: 98%